2019
DOI: 10.1021/acs.joc.9b03446
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effects of Ammonium and Sulfonium Salts and External Electric Fields on Aza-Diels–Alder Reactions

Abstract: The mechanism of the aza-Diels−Alder reaction catalyzed by tetraalkylammonium or trialkylsulfonium salts is explored with density functional theory. Favorable electrostatic interactions between the dienophile and the charged catalyst stabilize the highly polar transition state, leading to lower free energy barriers and higher dipole moments. Endo selectivity is predicted for both uncatalyzed and catalyzed systems. We also computationally evaluate the effects of oriented external electric fields (EEFs) on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…In the literature, the aza‐Diels‐Alder reaction between Danishefsky's diene and imines was shown to be catalysed through HB with tetraalkylammonium [28] and trialkylsulfonium [29] salts and through XB with iodotriazolium or iodoimidazolium salts [30] . Recently, through theoretical calculations, the role of Coulombic (dipole‐cation) interactions was also highlighted with onium catalysts [31] . Therefore, the polyhalogenated (bi)pyridinium salts reported here can in principle activate a substrate through the different modes of activation depicted in Figure 2.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…In the literature, the aza‐Diels‐Alder reaction between Danishefsky's diene and imines was shown to be catalysed through HB with tetraalkylammonium [28] and trialkylsulfonium [29] salts and through XB with iodotriazolium or iodoimidazolium salts [30] . Recently, through theoretical calculations, the role of Coulombic (dipole‐cation) interactions was also highlighted with onium catalysts [31] . Therefore, the polyhalogenated (bi)pyridinium salts reported here can in principle activate a substrate through the different modes of activation depicted in Figure 2.…”
Section: Introductionmentioning
confidence: 55%
“…These first series of experiments suggest that dipole‐cation interaction [31] or even charge transfer could be responsible for reaction initiation, but not HB. The inactivity of the iodide salt 9 a could be due to the charge transfer occurring between the pyridinium and iodide, which do not allow the imine substrate to interact with the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Donati reported the existence of intramolecular + N−C−H ⋅⋅⋅(O or N) H‐bonds in solution by 1 H NMR spectroscopy and by X‐ray crystallography [81] . Shirakawa and others demonstrated that some quaternary ammonium salts bearing an additional electron‐withdrawing group next to the ammonium accelerated the Mannich reaction via H‐bonding Lewis catalysis [82–84] . It is possible that the + N−C−H in Shirakawa's catalyst was too acidic to be configurationally stable in a basic media typically required for PTC reactions and for this reason this study was limited to achiral examples.…”
Section: Introductionmentioning
confidence: 99%
“… [81] Shirakawa and others demonstrated that some quaternary ammonium salts bearing an additional electron‐withdrawing group next to the ammonium accelerated the Mannich reaction via H‐bonding Lewis catalysis. [ 82 , 83 , 84 ] It is possible that the + N−C−H in Shirakawa's catalyst was too acidic to be configurationally stable in a basic media typically required for PTC reactions and for this reason this study was limited to achiral examples. Evidence for the interaction between + N−C−H and alkyl chlorides was obtained via 1 H NMR titrations, [82] which is important to determining the association of ammonium halides and their reagents.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, artificially designed electric fields have also been utilized to mediate non‐redox reactions through, for example, the electrode/electrolyte interface, [3] a voltage‐biased STM tip, [4] and the active site under the electric field possibly created by charged functional groups [5] or catalysts [6] . From a theoretical point of view, a large number of studies have been dedicated to the understanding and prediction of the effect of an oriented external electric field (OEEF) on various chemical transformations [7] such as C−H bond activation reactions, [6a–c, 7a–c] Diels–Alder reactions, [5e, 6d, 7d,e] methyl transfer reactions, [7f] electrophilic aromatic substitution reactions, [7g] nucleophilic substitutions of halogen‐bond complexes, [7h] and oxidative addition reactions [7i] …”
Section: Introductionmentioning
confidence: 99%